2022
DOI: 10.3390/horticulturae8010047
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Soluble Sugar Content, Related Enzyme Activity and Gene Expression in the Fruits of ‘Minihyang’ Mandarin on Different Rootstocks

Abstract: ‘Minihyang’ mandarin bears fruits with small size and high sugar content. ‘Minihyang’ mandarin grafted on trifoliate orange (TO) tends to be vigorous and develops water sprout open. It is associated with insufficient floral differentiation and fruit set. Recently, the use of Flying Dragon (FD) as rootstock with a high dwarf effect has been proposed to improve this situation. Therefore, this study was conducted to evaluate the effect of two different rootstock genotypes on tree growth, fruit yield, and fruit qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Recently, the Citrus Research Institute in South Korea developed Citrus "Minihyang" for the rst time. The novel cultivar was selected through the hybridization between Citrus kinokuni ex Tanaka "Kishu mikan" and Citrus reticulate "Ootaponkan" in 2015 and was registered in 2019 [4]. For "Minihyang," the ripening period is late November, and the harvest period lasts until January.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Citrus Research Institute in South Korea developed Citrus "Minihyang" for the rst time. The novel cultivar was selected through the hybridization between Citrus kinokuni ex Tanaka "Kishu mikan" and Citrus reticulate "Ootaponkan" in 2015 and was registered in 2019 [4]. For "Minihyang," the ripening period is late November, and the harvest period lasts until January.…”
Section: Introductionmentioning
confidence: 99%
“…For "Minihyang," the ripening period is late November, and the harvest period lasts until January. The fruit size is approximately 30-40 g, slightly larger than kumquats but smaller than common citrus fruits [4,5,6]. The average "Minihyang" sugar content is ≥ 13 °Bx, although it can reach a characteristically high degree of ≥ 15 °Bx depending on the cultivation conditions (in the case of indoor cultivation) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Citrus Research Institute in South Korea developed Citrus 'Minihyang' for the rst time. The novel cultivar is a citrus variety selected through the hybridization between Citrus kinokuni and Citrus poonensis in 2015 and was registered in 2019 [4]. For 'Minihyang,' the ripening period is late November, and the harvest period lasts up to January.…”
Section: Introductionmentioning
confidence: 99%
“…For 'Minihyang,' the ripening period is late November, and the harvest period lasts up to January. The fruit size is approximately 30-40 g, slightly larger than kumquats but smaller than common citrus fruits [4,5]. The sugar content is ≥ 13 °Bx on average, although it can reach a characteristically high level of ≥ 15 °Bx depending on the cultivation conditions (in the case of indoor cultivation) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Dwarf apple rootstocks can improve fruit color, significantly increase single-fruit weight and first-grade fruit yield, increase fruit hardness, and improve intrinsic fruit quality [17,18]. Dwarf citrus rootstocks can maintain tree-vigor stability and have no significant effect on nutrient content [19]. Yakushiji et al [20] also found that the difference in fruit quality between dwarf rootstocks and standard rootstocks of persimmons was not significant.…”
Section: Introductionmentioning
confidence: 99%